The Cabala - Wilder, Thornton (Open Road Integrated Media, Inc., 1929)
Intro – Title – Book One: First Encounters – Book Two: Marcantonio – Book Three: Alix – Book Four: AstrÉE-luce and the Cardinal – Book Five: The Dusk of the Gods – Copyright.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books